Tissue-specific changes in Srebf1 and Srebf2 expression and DNA methylation with perinatal phthalate exposure. Issue 2 (20th June 2019) - Moody, Laura; Hernández-Saavedra, Diego; Kougias, Daniel G; Chen, Hong; Juraska, Janice M; Pan, Yuan-Xiang
Abstract: Perinatal exposure to endocrine disrupting chemicals negatively impacts health, but the mechanism by which such toxicants damage long-term reproductive and metabolic function is unknown. Lipid metabolism plays a pivotal role in steroid hormone synthesis as well as energy utilization and storage; thus, aberrant lipid regulation may contribute to phthalate-driven health impairments. In order to test this hypothesis, we specifically examined epigenetic disruptions in lipid metabolism pathways after perinatal phthalate exposure. During gestation and lactation, pregnant Long–Evans rat dams were fed environmentally relevant doses of phthalate mixture: 0 (CON), 200 (LO), or 1000 (HI) µg/kg body weight/day. On PND90, male offspring in the LO and HI groups had higher body weights than CON rats. Gene expression of lipid metabolism pathways was altered in testis and adipose tissue of males exposed to the HI phthalate dosage. Specifically, Srebf1 was downregulated in testis and Srebf2 was upregulated in adipose tissue. In testis of HI rats, DNA methylation was increased at two loci and reduced at one other site surrounding Srebf1 transcription start site. In adipose tissue of HI rats, we observed increased DNA methylation at one region within the first intron of Srebf2 . Computational analysis revealed several potential transcriptional regulator binding sites, suggesting functional relevance of the identified differentially methylated CpGs. Overall, we show that perinatal phthalate exposure affects lipid metabolism gene expression in a tissue-specific manner possibly through altering DNA methylation of Srebf1 and Srebf2 .